Le commerce de la vérité: économie et commerce dans les Lois de Platon - Helmer, Etienne (PLATO JOURNAL, 2018)
Unlike the accepted idea that Plato’s view of trade and business is totally negative, my claim is that the whole set of limitations the Athenian prescribes to trade in the Laws only aims at minimizing its bad effects. Far from completely disapproving trade in itself, Plato acknowledges it has a practical positivity. Besides the needs, which are the first and most evident ends of trade and business, Plato shows that these activities also have to do with truth and justice, and can fulfill a truly positive moral and political function in the city of Magnesia under certain conditions.